Overview of post-partum mother adaptation: A healthy lifestyle needs - Rosnani, Rosnani; Mediarti, Devi (Palembang MediRose Publisher, 2022)
Natural transition from labour to post-partum can cause lifestyle changes that impact the mother’s physiological and psychological effects. Physical changes that include changes in diet, fluids, elimination, and obesity, as well as psychological changes such as anxiety, sleep disturbances, and depression, are common during this transitional period. For this reason, we use the Healthy Lifestyle approach to provide an overview and information regarding the mother’s adaptation during the post-partum period. Healthy lifestyle emphasizes that lifestyle has an important impact on health in which there is a role for individuals and others. In this case, nurses have a vital role in identifying and conducting analysis to determine the proper lifestyle and make mothers adapt easily during the transitional period from childbirth to post-partum. The main point of the intervention is to improve the well-being of the mother and baby.